Mining method selection for extracting moderately deep ore body using analytical hierarchy process at mindola sub- vertical shaft, Zambia. Issue 1 (31st December 2022) - Mutambo, Víctor; Kangwa, Samuel; Fisonga, Marsheal
Abstract: Mindola mine ore formation in Zambia comprises an interbedded sequence of argillites thinly banded to laminated dolomite and argillite. As a result of varying ore body characteristics, the mine has previously used different mining methods leading to increased mining cost. This study applies the Analytic Hierarchy Process (AHP) to determine a production method that fulfills the applicability requirement for mining a section of an ore-body below 4370 fL with the following characteristics: tabular; 45–90° of plunge; 10–20 m of ore thickness; intermediate grade; with moderate-to-strong ore and moderate side rocks. The mining method selected had to meet the following requirements: high recovery and lower powder factor. The AHP was applied because it can detect inconsistent judgements and provide a remedy for correction when dealing with complex decision making. The pairwise comparison matrix for criteria and weights was determined, followed by comparison of mining methods against each criterion. Synthesis of results for selecting a mining method was then done. Based on the assessed criteria, rock mass rating (RMR) ranked highest with 23.83%, thickness with 15.31% and powder factor with 15.11%. When the criteria were evaluated with the alternatives, the technically applicable mining method with the highest score of 18 % was Vertical Crater Retreat (VCR), followed by sublevel open stoping with 16.62%. Sensitivity analysis revealed that as the variables were altered by 1 to 6% and 5 to 25%, VCR remained as the technically applicable method rather than the production method that meets both economic and engineering conditions.